Pendampingan UMKM dalam Pemasaran Produk Melalui Media Sosial dan Marketplace - Yossi Indrawati Syuhardi; Danang Sutrisno; Michael Sonny; Riezca Talita Trista; Eko Tri Asmoro (Jurnal Ragam Pengabdian, 2025)
This community service activity aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in utilizing social media and marketplaces as digital marketing tools. The program involved hands-on training, digital platform simulations, and assistance in creating business accounts and promotional content. A total of 15 MSME participants were involved. Initial findings showed that 80% of the participants had no business social media accounts, and 73% had never used marketplace platforms. However, following the mentoring sessions, there was a significant increase in participants’ knowledge and skills, with 93% stating that the program was highly practical and helpful. This activity also fostered digital entrepreneurship enthusiasm and opened new opportunities for MSMEs to grow sustainably in the digital era.